Sir John Salmond and Maori Land Tenure - Boast, Richard P (Victoria University of Wellington Law Review, 2019)
This chapter is deals with Salmond's engagement with Maori land issues, principally in his capacity as counsel to the Law Drafting Office and while Solicitor-General. Salmond appears to have had firm views on the extent of Native title in New Zealand, arguing either that all land vested in dominium in the Crown on the acquisition of British sovereignty, or, as a kind of fall-back position, that there were at least some parts of the Dominion, such as navigable lakes or the foreshore, where native title could not be asserted in any circumstances, not even in the Native Land Court. While it is tempting to conclude that Salmond's views were nothing more than the orthodoxy of the day, this paper argues that matters were more contested than is sometimes thought. Salmond developed considerable expertise in the technicalities of Maori land law, an expertise developed initially in the drafting of the Native Lands Bill of 1909 and which is reflected in various opinions he prepared while Solicitor-General and in his famous dissenting judgment in Boyd v Mayor of Wellington.